Exposição fotográfica sobre a revolta militar de 1926 em Santa Maria, RS, Brasil - Santos, Wagner Serafini dos (2016)
This master degree s conclusion study is part of History Heritage and Cultural Heritage Research Line of Professional Masters Course in Cultural Heritage of Universidade Federal de Santa Maria. The purpose of this study was carrying out a photographic exhibition about the military revolt that took place in Santa Maria city (RS) in November 1926, from research conducted in Correio da Serra, Gaspar Martins, Diário do Interior and O Castilhista newspapers, in photographs and several documents of that time in order to spread this local history chapter. It was surveyed the collections of the Arquivo Histórico Municipal de Santa Maria, the library of the Colégio Marista Santa Maria (Biblioteca Irmão Daniel), Casa de Memória Edmundo Cardoso, Centro Histórico Coronel Pillar, Memorial Mallet and the Museu Educativo Gama d Eça. The revolt began with the uprising of two Brazilian Army barracks, the 5º Regimento de Artilharia Montada (current 3º Grupo de Artilharia de Campanha Autopropulsado Regimento Mallet) and the 7º Regimento de Infantaria (current 7º Batalhão de Infantaria Blindado Regimento Gomes Carneiro), which attacked the 1º Regimento de Cavalaria of the Brigada Militar (current 1º Regimento de Polícia Montada Regimento Coronel Pillar) forces, resulting in a bombardment over downtown area. The battle ended with the withdrawal of the rebellious military, who left Santa Maria due to the Brigada Militar resistance. We worked to show the military revolt events from the Santa Maria´s press viewpoint of that time, alongside the focus of books describing the fact. The exhibition was created to be displayed on a mobile way in Santa Maria town. According to the placed methodology, the research is applied, exploratory, bibliographic and documentary. The dissertation reports as newspapers, pictures and other surveyed documents relate to Santa- Mariense cultural heritage, reproduces the information collected in these sources and contextualizes the military revolt of 1926 history, showing that this was part of the tenentista movement of the 1920s.